2021
DOI: 10.1186/s12893-021-01205-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perioperative outcomes of single-port laparoscopy, three-port laparoscopy and conventional laparotomy in removing giant ovarian cysts larger than 15 cm

Abstract: Background Although conventional laparoscopy has gradually accepted as a surgical treatment for ovarian cancer, reducing the port numbers of laparoscopy still has great challenge for larger ovarian tumors. Thus, this study aims to explore the surgical outcomes of single-port laparoscopy for removing giant ovarian cysts (≥ 15 cm) and compare with laparotomy and three-port laparoscopy. Methods This study enrolled 95 patients with giant ovarian cysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Introducing unique techniques, such as using a single port laparoscopy as opposed to a 3-port laparoscopy, will have a substantial effect on the risk of rupture (3.0 vs 22.2%). However, there is no difference in overall hospital cost, time till gas passing or postoperative problems among the various surgical procedures [15] . Using a laparoscopic endobag for the treatment has produced impressive outcomes, as it has shortened the average operating time by 18 minutes and eliminated 43.3% of potential spillage [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Introducing unique techniques, such as using a single port laparoscopy as opposed to a 3-port laparoscopy, will have a substantial effect on the risk of rupture (3.0 vs 22.2%). However, there is no difference in overall hospital cost, time till gas passing or postoperative problems among the various surgical procedures [15] . Using a laparoscopic endobag for the treatment has produced impressive outcomes, as it has shortened the average operating time by 18 minutes and eliminated 43.3% of potential spillage [16] .…”
Section: Discussionmentioning
confidence: 99%
“…A direct correlation existed between ovarian cyst size and rupture risk, as 80% of ovarian dermoid cysts ruptured above the size of 60mm compared to the group with a diameter less than 60mm (51.17% of cysts ruptured) [ 12 ]. A dermoid cyst subgroup analysis highlighted a significant correlation between cyst rupture and chemical peritonitis (risk rate: 9.36; 95% confidence interval: 1.20-73.28) [ 13 ]. Introducing novel techniques, such as using a single port over a three port in laparoscopy, will significantly impact the rupture risk (3.0 vs. 22.2%); however, there will be no variations in postoperative complications [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study ( 27 ) showed that 7 patients with a diameter of ovarian cysts > 10 cm successfully underwent laparoendoscopic single-site extracorporeal cystectomy with an average operative time of 76.42 minutes, no overflow of cyst contents, and no perioperative complications. In addition, two retrospective case–control studies ( 14 , 16 ) compared LESS-E cystectomy with conventional laparoscopy and laparotomy and indicated that LESS-E cystectomy resulted in a shorter operation time, less blood loss and a lower leakage rate. Furthermore, our previous propensity score matching study ( 23 ) compared LESS-E cystectomy and LESS-I cystectomy and revealed the same results: LESS-E cystectomy was associated with a shorter operation time and lower leakage rate.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some previous studies showed the superiority of a laparoendoscopic single-site extracorporeal (LESS-E) technique that combines the virtue of laparoendoscopic and laparotomy ( 13 16 ). The surgeons do the operation through the process of an open surgery, who get convenient and direct cystectomy, and the patients suffer less pain and recover faster, who get the advantage of minimally invasive surgery.…”
Section: Introductionmentioning
confidence: 99%